2012
DOI: 10.1192/pb.bp.111.037374
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome in patients attending psychiatric day centres: prevalence and associations

Abstract: Aims and methodTo ascertain the prevalence of metabolic syndrome in individuals with chronic enduring mental illness attending community psychiatric day centres, and to identify the prevalence of individual cardiometabolic risk factors and the rate of screening for these abnormalities. One hundred participants with chronic enduring mental illness were recruited and investigated using physical assessments and comprehensive laboratory testing.ResultsOf the 100 participants recruited, 55% met the criteria for met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In a study which evaluated the prevalence of MetS in a 100 patients attending psychiatric day centers showed that 55% met the criteria for MetS with similar prevalence rates between those with psychotic and non-psychotic disorders ( 13 ). A cross-sectional study evaluated the prevalence of MetS in community psychiatric nurses showed that they have a double relative risk of developing MetS in comparison with the general population.…”
Section: Introductionmentioning
confidence: 99%
“…In a study which evaluated the prevalence of MetS in a 100 patients attending psychiatric day centers showed that 55% met the criteria for MetS with similar prevalence rates between those with psychotic and non-psychotic disorders ( 13 ). A cross-sectional study evaluated the prevalence of MetS in community psychiatric nurses showed that they have a double relative risk of developing MetS in comparison with the general population.…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly important as many people with SMI do not attend primary care and monitoring of CVD risk factors remains low in other settings. 19,[111][112][113][114] The SMI-specific BMI model provides an opportunity to target more people with SMI, to increase identification of those at a high risk of CVD and decrease the physical, social and financial burden associated with CVD.…”
Section: Work Package 1: Additional Economic Modelling Work Over and mentioning
confidence: 99%
“…For these reasons, national and international guideline groups, including the National Institute for Health and Clinical Excellence (NICE) in England, advise that patients with severe mental illness should undergo regular screening for diabetes and other risk factors for cardiovascular disease [NICE, 2011[NICE, , 2014. Despite this clear guidance, many studies have shown that monitoring of physical health in people with severe mental illness is less than optimal, probably due to a number of interacting clinical and organizational factors [Barnes et al 2007[Barnes et al , 2008Gubbins et al 2012].…”
Section: Therapeutic Advances In Psychopharmacologymentioning
confidence: 99%
“…illness is less than optimal, probably due to a number of interacting clinical and organizational factors [Barnes et al 2007[Barnes et al , 2008Gubbins et al 2012].…”
mentioning
confidence: 99%